PENGGUNAAN METODE SOSIODRAMA DALAM MENINGKATKAN KEMAMPAUAN BEBICARA PADA PELAJARAN BAHASA INDONESIA SISWA KELAS VIII-2 SMP NEGERI 1 PAHAE JAE T.A 2018/2019 - Sibarani, Roden Sia (JGK (Jurnal Guru Kita), 2020)
Abstract: The Use of Sociodrama Methods to Improve Speaking Ability in Indonesian Language Lessons for Class Viii-2 Junior High School 1 Pahae Jae T.A 2018/2019. This research was conducted at SMP Negeri 1 Pahae Julu, with the aim of knowing the students’ speaking ability in order to increase their learning activities using the sociodrama method. This type of research is Classroom Action Research (PTK), the subjects in this study were VIII-2 students of SMP Negeri 1 Pahae. Julu. in the 2018/2019 school year. With a total of 32 students consisting of 16 boys and 16 girls. Determination of the subject is obtained based on the results of observations of the class to be studied and based on the results of references from the class teacher. The object of this research is the action to improve speaking skills through the sociodrama method, the subject of reading conversational texts using the sociodrama method. Based on the data analysis, it was found that the scores of 32 students in the first cycle of meeting I were 8 students who obtained the criteria of being able (23.33%) , 3 students obtained the criteria of being quite capable (10.00%), 22 students obtained the criteria for being less fortunate (66.67%). In the second cycle of the second meeting, there were 1 student who obtained the very capable criteria (3.33%). In the second cycle of the first meeting there were 17 students who obtained the criteria of being able (53.33%), 8 students obtained the criteria of being quite capable (23.33%) and there were 2 students who obtained the criteria of being less well off (6.67%). In the second cycle of the second meeting there were 13 students who obtained the very capable criteria (60.00%), 19 students obtained the criteria of being able (40.00%). The teacher’s score also increased in the first cycle of meeting I 30 (75%) in the first cycle of meeting II getting a score of 33 (82.5%) in the second cycle of meeting I 35 (85%) in the second cycle of meeting II getting a score of 39 (95%). Very well categorized. Thus it can be concluded that using the sociodrama method can improve students’ speaking skills after the implementation of the teaching and learning process in Indonesian language lessons reading conversational text material at VIII-2 SMP Negeri 1 Pahae Julu T.A 2018/2019. Keywords: Sociodrama Method, Speaking Ability Abstrak: Penggunaan Metode Sosiodrama Dalam Meningkatkan Kemampauan Bebicara Pada Pelajaran Bahasa Indonesia Siswa Kelas Viii-2 Smp Negeri 1 Pahae Jae T.A 2018/2019. Penelitian ini dilaksanakan di SMP Negeri 1 Pahae Julu, dengan tujuan untuk mengetahui kemampuan berbicara siswa upaya meningkatkan aktivitas belajar dengan menggunakan metode sosiodrama.Jenis penelitian ini adalah Penelitian Tindakan kelas (PTK), subjek dalam penelitian ini adalah siswa VIII-2 SMP Negeri 1 Pahae Julu. pada tahun ajaran 2018/2019. Dengan jumlah siswa sebanyak 32 Orang yang terdiri dari 16 orang laki-laki dan 16 orang perempuan. Penentuan subjek diperoleh berdasarkan hasil pengamatan terhadap kelas yang akan diteliti dan berdasarkan hasil rujukan dari guru kelas. Objek penelitian ini adalah tindakan sebagai meningkatkan kemampuan berbicara melalui metode sosiodrama pokok bahasan membaca teks percakapan dengan menggunakan metode sosiodrama.Berdasarkan analisis data diperoleh bahwa nilai dari 32 siswa pada siklus I pertemuan I terdapat 8 orang siswa yang memperoleh kriteria mampu (23,33%), 3 orang siswa memperoleh kriteria cukup mampu (10.00%), 22 orang siswa memperoleh kriteria kurang mampu (66,67%). Pada Siklus II pertemuan II terdapat 1 orang siswa memperoleh kriteria sangat mampu (3,33%). Pada siklus II pertemuan I terdapat 17 orang siswa memperoleh kriteria mampu (53,33%), 8 orang siswa memperoleh kriteria cukup mampu (23,33%) dan terdapat 2 orang siswa yang memperoleh kriteria kurang mampu (6,67%). Pada siklus II pertemuan II terdapat 13 orang siswa memperoleh kriteria sangat mampu (60,00%), 19 orang siswa memperoleh kriteria mampu (40,00%),. Skor guru juga mengalami peningkatan dalam siklus I pertemuaan I 30 (75%) siklus I pertemuan II memperoleh skor 33 (82,5%) siklus II pertemuan I 35 (85%) siklus II pertemuan II memperoleh skor 39 (95%). Dikatagorikan sangat baik. Dengan demikian dapat disimpulkan bahwa dengan menggunakan metode sosiodrama dapat meningkatkan kemampuan berbicara siswa setelah dilaksanakannya proses belajar mengajar pada pelajaran Bahasa Indonesia materi membaca teks percakapan di VIII-2 SMP Negeri 1 Pahae Julu T.A 2018/2019. Kata Kunci : Metode Sosiodrama, kemampuan Berbicara